1997
DOI: 10.1002/(sici)1097-4555(199709)28:9<647::aid-jrs155>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic study of pyroxene structures from the Munni Munni layered intrusion, Western Australia

Abstract: Raman spectra were obtained for a series of clinopyroxenes, orthopyroxenes and inverted pigeonites from the Munni Munni layered maÐc-ultramaÐc intrusion in Western Australia. Their composition varies from to mg 48 where mg = mg number = atomic 100 Mg/(Mg + Fe) and Fe = total Fe. The characteristic Raman bands mg 87 , of pyroxene are mainly due to vibrations of the tetrahedra and occur in the 300-400, 650-700 and 980-1020 SiO 4 wavenumber regions of the spectra. Clinopyroxene shows only one intense Raman band i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 4 publications
3
39
0
Order By: Relevance
“…Figure 1 illustrates that these frequencies depend nearly linear on the composition for a number of solid solution phases. According to Huang et al (2000) and Mernagh and Hoatson (1997) a similar trend is present in pyroxenes and according to Hofmeister and Mao (2001) in silicates with the spinel structure. Guyot et al (1986) have shown that a quantitative theoretical interpretation of the substitutional effect of magnesium by iron is not straightforward.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Figure 1 illustrates that these frequencies depend nearly linear on the composition for a number of solid solution phases. According to Huang et al (2000) and Mernagh and Hoatson (1997) a similar trend is present in pyroxenes and according to Hofmeister and Mao (2001) in silicates with the spinel structure. Guyot et al (1986) have shown that a quantitative theoretical interpretation of the substitutional effect of magnesium by iron is not straightforward.…”
Section: Introductionsupporting
confidence: 59%
“…Figure 1a indicates that for three internal vibrational modes in olivine these frequencies show a near-linear behavior with composition. According to Huang et al (2000) and Mernagh and Hoatson (1997) such a trend is also present in at least 17 internal-and lattice vibrational modes of pyroxenes and Fig. 1b exemplifies that this is the case for a number of these modes.…”
Section: Theoretical Backgroundmentioning
confidence: 53%
“…The spectrum (g) is assigned to clinopyroxene with is Raman bands at about 323, 353, 390, 508, 530, 557, 663, 821, 862, 926, 1007, and 1038 cm 1 . 25 Clinopyroxene is still observed in the spectrum (h), showing a slightly different pattern. The spectrum (i) shows two broad bands at 484 and 676 cm 1 .…”
Section: Resultsmentioning
confidence: 98%
“…25,26 The spectrum (b) is due to a superposition of materials: the Raman bands at about 289, 405, 493, 512, and 599 cm 1 can be assigned to the hematite, while the band at about 660 cm 1 is assigned to the presence of magnetite. 27 -32 These two iron minerals are generally associated with the investigated samples but in some cases the spectrum of isolated magnetite is obtained, as in spectrum (c).…”
Section: Resultsmentioning
confidence: 99%
“…5b). According to systematic Raman studies of pyroxenes, these bands, especially the splitting of the doublet in the 650-680 cm )1 region, are typical for orthopyroxene (Mernagh and Hoatson 1997).…”
Section: Brownish Inclusionsmentioning
confidence: 99%